Indeterminaçáo e fenomenôs fronteiriços: Consideraçóes se gundo o ponto de vista do pragmatismo peirceano - Pires, Jorge de Barros [UNESP]; Silveira, Lauro Frederico Barbosa da [UNESP] (FapUNIFESP (SciELO), 2013)
Pragmatism, as a formal method, has provided a fabulous arena for discussions about the way concepts may be constructed, irrespective of any anthropomorphic or linguistic position. We will see that the pragmatic maxim possesses an interesting thesis regarding the indetermination of the meaning. Such idea helps to understand the transit between the indefinite and the defined, indeterminate and determined, as well as some found intermediate borders in the processes of relative determination.
Scientific Concepts and Bordering Phenomena: Some Considerations from the Peircean Pragmatic Point of View
Keywords: Bordering phenomena; Indetermination; Pragmatism; Scientific concepts; Vagueness